In silico investigation of binding affinities between human leukocyte antigen class I molecules and SARS-CoV-2 virus spike and ORF1ab proteins - Spyros A. Charonis; Effie-Photini Tsilibary; Apostolos P. Georgopoulos (Exploration of Immunology, 2021)
Aim: The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019, a global pandemic. There is hence an urgent need for effective approaches to understand the mechanism of viral interaction with immune cells that lead to viral elimination and subsequent long-term immunity. The first, immediate response to the viral infection involves mobilization of native immunity and human leukocyte antigen (HLA) class I mechanisms to kill infected cells and eliminate the virus. The second line of defense involves the activation of HLA class II system for the production of antibodies against the virus which will add to the elimination of the virus and prevent future infections. In a previous study, investigated the relations between SARS-CoV-2 spike glycoprotein (S protein) and HLA class II alleles were investigaed; here report on the relations of the S protein and the open reading frame 1ab (ORF1ab) of SARS-CoV-2 to HLA class I alleles. Methods: An in silico sliding window approach was used to determine exhaustively the binding affinities of linear epitopes of 10 amino acid length (10-mers) to each of 61 common (global frequency ≥ 0.01) HLA class I molecules (17, 24 and 20 from gene loci A, B and C, respectively). A total of 8,354 epitopes were analyzed; 1,263 from the S protein and 7,091 from ORF1ab. Results: HLA-A genes were the most effective at binding SARS-CoV-2 epitopes for both spike and ORF1ab proteins. Good binding affinities were found for all three genes and were distributed throughout the length of the S protein and ORF1ab polyprotein sequence. Conclusions: Common HLA class I molecules, as a population, are very well suited to binding with high affinity to SARS-CoV-2 spike and ORF1ab proteins and hence should be effective in aiding the early elimination of the virus.